Redo Coronary Artery Bypass Grafting in the era of Advanced PCI - Kusu-Orkar,Ter-Er (2022)
Abstract Objective: To review the evidence behind the role and relevance of redo coronary artery bypass grafting (CABG) in the current practice of percutaneous coronary intervention (PCI). Methods: A comprehensive electronic literature search was performed to identify articles that discuss the practice of PCI and redo CABG in patients that require coronary revascularization. All relevant studies are summarized in narrative manner to reflect current indications and preference. Results: The advancement in utilization of PCI has reduced the rate of redo CABG in patients with previous CABG that requires revascularization of an already treated coronary disease or a new onset of coronary artery stenosis. Redo CABG is associated with satisfactory perioperative outcomes but higher mortality at immediate postoperative period when compared to PCI. Conclusion: Redo CABG patients are less likely to develop comorbidities associated with revascularisation, but the operative mortality is higher and long-term survival rates are similar in comparison to PCI. There is a need for further research into the role of redo CABG in the current advanced practice of PCI.